2023
DOI: 10.1097/md.0000000000036241
|View full text |Cite
|
Sign up to set email alerts
|

Association between elevated endocan levels and obstructive sleep apnea hypopnea syndrome in Turkey and China: A meta-analysis

Jie He,
PeiPei Li,
Weinan Lu
et al.

Abstract: Background: Endothelial dysfunction has been implicated in the pathogenesis of obstructive sleep apnea–hypopnea syndrome (OSAHS). Previous research has linked endothelial dysfunction to the vascular pathology marker endothelial cell-specific molecule-1 (endocan). This meta-analysis compared endocan concentrations among adult patients with OSAS and controls, and ascertained whether any differences exist. This study aimed to highlight the association between high endocan levels and OSAHS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Another reason is that for children, PSG examinations require them to sleep throughout the night, and the results may not be promptly available for feedback.Therefore, identifying a simple, easily obtainable outpatient indicator that aligns with PSG results would aid cliniciansin the initial evaluation of the condition and the development of subsequent treatment plans. It had been shown that Endocan and YKL-40 levels in serum, and IL-6 and Vimentin levels in plasma revealed the most promising candidates for OSA diagnosis [5,6]. Fiedorczuk et al found that a total of 14 sets of candidate biomarkers displayed differences in levels or concentrations in OSAHS patients compared to non-OSA controls, and decreased after OSA treatment: IL-6, leptin, IL-8, IGF-1, etc [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another reason is that for children, PSG examinations require them to sleep throughout the night, and the results may not be promptly available for feedback.Therefore, identifying a simple, easily obtainable outpatient indicator that aligns with PSG results would aid cliniciansin the initial evaluation of the condition and the development of subsequent treatment plans. It had been shown that Endocan and YKL-40 levels in serum, and IL-6 and Vimentin levels in plasma revealed the most promising candidates for OSA diagnosis [5,6]. Fiedorczuk et al found that a total of 14 sets of candidate biomarkers displayed differences in levels or concentrations in OSAHS patients compared to non-OSA controls, and decreased after OSA treatment: IL-6, leptin, IL-8, IGF-1, etc [7].…”
Section: Introductionmentioning
confidence: 99%